Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1016/j.jconrel.2015.08.018
|View full text |Cite
|
Sign up to set email alerts
|

Drug transporters in tissues and cells relevant to sexual transmission of HIV: Implications for drug delivery

Abstract: Efflux and uptake transporters of drugs are key regulators of the pharmacokinetics of many antiretroviral drugs. A growing body of literature has revealed the expression and functionality of multiple transporters in female genital tract (FGT), colorectal tissue, and immune cells. Drug transporters could play a significant role in the efficacy of preventative strategies for HIV-1 acquisition. Pre-exposure prophylaxis (PrEP) is a promising strategy, which utilizes topically (vaginally or rectally), orally or oth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(43 citation statements)
references
References 237 publications
(281 reference statements)
0
43
0
Order By: Relevance
“…Similar high RAL penetration was seen in our study in rectal and intestinal tissues. This higher and differential accumulation in various tissues compared to plasma akin to that seen in human studies may be attributable to several factors that include differential and selective expression and localization of drug transporters in distinct mucosal compartments (45,46). …”
Section: Discussionmentioning
confidence: 93%
“…Similar high RAL penetration was seen in our study in rectal and intestinal tissues. This higher and differential accumulation in various tissues compared to plasma akin to that seen in human studies may be attributable to several factors that include differential and selective expression and localization of drug transporters in distinct mucosal compartments (45,46). …”
Section: Discussionmentioning
confidence: 93%
“…We and others have reported that several efflux transporters, including P-gp, BCRP, and MRP4, were positively or even highly expressed in the cervicovaginal and colorectal tissues of human, macaque, rabbit, and mouse, as well as the cell lines derived from human cervicovaginal or colorectal tissues [2430]. These animal models are used in PrEP microbicide testing.…”
Section: Introductionmentioning
confidence: 99%
“…Although highly variable, some reports suggest that tenofovir diphosphate (TFVdp) kinetics differs across cell types within cervical tissue. Louissaint et al estimated median (interquartile range) TFVdp halflives of 34 (21,40), 82 (43,89), and 60 (52,72) when measured by cervical tissue homogenate, total disaggregated cells from a cervical biopsy, and isolated cervical CD4 cells, respectively. 14 More research in this area is needed but is limited by the small number of cells in a typical biopsy and assay limitations for quantification.…”
Section: Heterosexual Transmission and Anatomy Of The Female Genital mentioning
confidence: 99%